Comparison of Spinopelvic Configuration and Roussouly Alignment Types Between Pediatric and Adult Populations. Issue 18 (15th September 2022) - Charles, Yann Philippe; Lamas, Vincent; Ilharreborde, Brice; Blondel, Benjamin; Prost, Solène; Bauduin, Eloïse; Laouissat, Féthi; Riouallon, Guillaume; Wolff, Stéphane; Challier, Vincent; Obeid, Ibrahim; Boissière, Louis; et al.
Abstract : Study Design: Retrospective cross-sectional study. Objective: The aim was to describe spinopelvic alignment types by pelvic incidence (PI) and age to compare the Roussouly classification between pediatric and adult populations. Summary of Background Data: The Roussouly classification was validated for adults. Alignment types may vary during growth. Materials and Methods: Radiographs of 1706 non pathologic individuals (5–49 yr) were analyzed. Individuals ≤19 years were stratified by chronological age and skeletal maturity (triradiate cartilage, Risser), and compared with adults. Global and spinopelvic alignment parameters were assessed. Roussouly Types 1, 2, 3, 3A (anteverted pelvis), and 4 were determined. The distribution of parameters was analyzed by Bayesian inference. The relationship between PI and age by Roussouly type was modeled by linear regression. Results: The Sagittal Vertical Axis C7 decreased during growth and was significantly smaller in adults (20–34 yr) (Pr>0.99). Thoracic kyphosis and lumbar lordosis increased during growth and were larger in adults (Pr<0.025). Lordosis increased mainly in the cranial arch (Pr<0.025). PI and pelvic tilt increased during growth and were larger in adults (Pr<0.025). In children and adolescents, PI<45° represented the largest proportion, significantly larger compared with adults (Pr>0.99). Proportions of Roussouly Types 1 and 2 were similar throughout ages. Types 3 and 4 were rarer during the prepubertal period (Pr<0.025). The proportion of Type 3A was significantly higher in children and adolescents (Pr>0.99). Linear regression showed that Type 4 had the largest PI increase with age, with significantly higher curve slope compared with other types (Pr>0.9999). Types 3, 3A and 2 had similar slopes and lowest PI increase with age. Conclusion: Global and spinopelvic alignment changed during childhood and adolescence, leading to different kyphosis and lordosis distribution compared with adults. Growth-related PI increase influenced Roussouly types with typical predominance of Type 3A in the pediatric population and larger PI increase in Type 4. Level of Evidence: Level III.